If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + 5x = 39 Solving -1 + 5x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 5x = 39 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = 39 + 1 5x = 39 + 1 Combine like terms: 39 + 1 = 40 5x = 40 Divide each side by '5'. x = 8 Simplifying x = 8
| (6n-4)+14=1 | | .24(10000)-.02y=.08(y+10000) | | -15-15x=-4x-8x | | 5x-15=25y | | 2(X+4)+2=4 | | -(3x-1)= | | 2(2x-2)=-16 | | 9-2(x-3)=9 | | 5x+5(3x-7)=125 | | .30(24)+.05x=.15(12+x) | | 2d^2=8-10d | | |x+1|=0 | | X=4.5+y | | 174=22x+8+6x-2 | | (3x^2+2x-6)+(x^2-4x)=x | | 60=7x+5 | | 4y^2+5y-12=0 | | 3 = q2 | | (-1)19= | | 7(2l+5)=91 | | (3x^2+2x-6)+(x^2-4x)= | | 4x^2+4x-9= | | d+3.77-1.99=5.38 | | 10y-7=9+2 | | 4(a-1)=76 | | 5x-8=6+8x+4x | | 162=x+142+x+44 | | 45=16t+23-9t | | p+4=9.5 | | 2x-18=3x-9 | | (5x+20)+(4x-2)=180 | | (u+3)*9=39 |